Using the Digital Game Wordwall to Enhance Efl Students’ Vocabulary Mastery - Sakkir, Geminastiti; Azis, Nurhikma; Jabu, Baso (Universitas Negeri Makassar, 2023)
This study aims to test the effectiveness of utilizing the digital game Wordwall in improving students' vocabulary at SMAN 1 Gowa, specifically in class XI MIPA 3. The research method employed a pre-experimental approach with pretest and posttest measurements. The population for this study consisted of all students at SMAN 1 Gowa, while a random sample of 35 students was selected from Class XI MIPA 3. The analysis revealed that the mean score on the pretest was recorded as 82.34, whereas it increased significantly to 98.31 on the posttest. By conducting a paired-sample t-test statistical analysis with a significance level set at α = 0.05, a significant difference between the mean scores of the pretest and posttest was found (p <0.05). This indicates that using Wordwall as a digital game effectively enhances students' vocabulary. In conclusion, this research supports the hypothesis that employing Wordwall as a digital game can improve students' vocabulary at SMAN 1 Gowa. The positive outcomes resulting from an increase in posttest scores have important implications for English teachers who may consider incorporating game-based technology like Wordwall as an engaging and interactive tool for vocabulary learning.